2020
DOI: 10.1088/1361-6528/ab8043
|View full text |Cite
|
Sign up to set email alerts
|

Influence of p-n junction mechanism and alumina overlayer on the photocatalytic performance of TiO2 nanotubes

Abstract: Modified hybrid structures of TiO2 nanotubes (TONT), p-Al doped TONT/n-TONT with an additional overlayer of alumina, are constructed to achieve 99.57% photodegradation of the stable organic pollutant methylene blue (MB) within 180 min, a degradation rate 17 times higher than pure TONTs. The anodization at three different temperatures 2, 28 and 40 °C followed by impregnation of Al is used for their preparation. The analyses of structure, chemical composition and morphology are completed using x-ray diffraction,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 62 publications
2
5
0
Order By: Relevance
“…Recently, we reported use of p-Al-doped TONT/n-TONT with an additional layer of alumina to obtain 99.57% degradation of the stable organic pollutant MB within 180 min. [42] In the present case, Figure 11. Photocatalytic mechanism of ITONTs.…”
Section: Photocatalytic Studiessupporting
confidence: 46%
See 2 more Smart Citations
“…Recently, we reported use of p-Al-doped TONT/n-TONT with an additional layer of alumina to obtain 99.57% degradation of the stable organic pollutant MB within 180 min. [42] In the present case, Figure 11. Photocatalytic mechanism of ITONTs.…”
Section: Photocatalytic Studiessupporting
confidence: 46%
“…Recently, we reported use of p‐Al‐doped TONT/n‐TONT with an additional layer of alumina to obtain 99.57% degradation of the stable organic pollutant MB within 180 min. [ 42 ] In the present case, the degradation efficiency of 96% in 180 min for the same pollutant is obtained with indium‐doped TiO 2 prepared by a more cost‐effective and time‐saving method. In the case of Al‐doped heterostructure, the catalyst preparation was done by anodization followed by impregnation and the average total time for the process was ≈6.5 h, [ 42 ] whereas for the fabrication of the ITONT in the present work ≈2.5 h is required.…”
Section: Resultsmentioning
confidence: 67%
See 1 more Smart Citation
“…Among the three peaks the low XPS spectra of Al 2p and its peak position at 74.4 eV are shown in figure 6(f). This value matches with the binding energy of Al in Al 2 O 3 [57,58] and, hence is a signature of the presence of the binary phase on the surface of AZnO films. The large percentage of composition of Al on the surface of doped samples with respect to that of Zn is due to the contributions from the binary as well as by the substituted Al ions in the lattice.…”
Section: Resultssupporting
confidence: 73%
“…These OH * radicals with high oxidation tendency combine with organic compounds which result in the formation of CO Srivatsav et al [66] reported that the formation of homojunctions between semiconductors is one of the strategies to enhance the separation of carriers. Nair et al [57] fabricated Al 2 O 3 /p-Al:TONT/n-TONT hybrid structure and obtained enhanced photocatalytic activity for the prepared structure than the undoped TiO 2 . In the junction, the formation of alumina insulating over-layer (Al 2 O 3 ) was one of the major reasons for the better degradation, as it acted as an adsorption site for the MB solution.…”
Section: Modes Of Vibration Of Znomentioning
confidence: 99%